Electrical Control and Monitoring Home System With ACS712 Sensor & Relay Module via Blynk - adi surya antara; wayan Arsa suteja; I Gede Eka Wiantara Putra; Ida Bagus Putu Widja; I Putu Agus Setiawan (Patria Artha Technological Journal, 2023)
Electrical load control and monitoring system is a device designed to control and monitor electricity consumption. The process of monitoring electric loads uses a power sensor model ACS712 which is connected to a relay module to supply electric loads and stop using electric loads if power consumption exceeds a predetermined capacity of 1000 watts so that energy control can be carried out. The microcontroller used is the NodeMCU esp8266 microcontroller which functions as the main control system that will be linked to the blynk application with the aim of being able to monitor it in real time in the future. By conducting an experiment assembling the ACS712 sensor module with NodeMCU esp8266 which produces a monitoring feature for reading current, power, energy and peak power measurements from the IoT blynk application through the ACS712 sensor. The results of this study are a control and monitoring of household electricity measurements through the blynk application to control the use of electrical energy loads from household electronic devices in the form of readings of current, power, energy, and stopping the supply of electric power to loads connected to the ACS712 sensor and relay. module. The Blynk IoT application, the ACS712 sensor is almost close to the measuring instrument or clamp meter used so that it is able to properly and correctly monitor electricity usage in household loads